2016
DOI: 10.1038/ncomms10337
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophilic arylation with tetraarylphosphonium salts

Abstract: Organic phosphonium salts have served as important intermediates in synthetic chemistry. But the use of a substituent on the positive phosphorus as a nucleophile to construct C–C bond remains a significant challenge. Here we report an efficient transition-metal-free protocol for the direct nucleophilic arylation of carbonyls and imines with tetraarylphosphonium salts in the presence of caesium carbonate. The aryl nucleophile generated from phosphonium salt shows low basicity and good nucleophilicity, as eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(40 citation statements)
references
References 51 publications
1
39
0
Order By: Relevance
“…One possible explanation is that this results from lower solubility of CO 2 at 60 °C and concomitantly less carbonate formed by reaction of CO 2 with HO − at higher temperatures. It is carbonate ions that react with phosphonium units to form phosphine oxides as a major decomposition pathway in these species . Phosphonium degradation also appeared to increase with PEN surface area, reflecting the greater accessibility of the PAr 4 + units to water and dissolved carbonate and hydroxide [Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation is that this results from lower solubility of CO 2 at 60 °C and concomitantly less carbonate formed by reaction of CO 2 with HO − at higher temperatures. It is carbonate ions that react with phosphonium units to form phosphine oxides as a major decomposition pathway in these species . Phosphonium degradation also appeared to increase with PEN surface area, reflecting the greater accessibility of the PAr 4 + units to water and dissolved carbonate and hydroxide [Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is carbonate ions that react with phosphonium units to form phosphine oxides as a major decomposition pathway in these species. 18 Phosphonium degradation also appeared to increase with PEN surface area, reflecting the greater accessibility of the PAr 4 + units to water and dissolved carbonate and hydroxide [ Fig. 4(A)].…”
Section: Water Uptake and Alkaline Stabilitymentioning
confidence: 99%
“…Therefore, the authors excluded an ET pathway.T hey [104] propose that the reaction may proceed through direct transfer of the "CF 2 H" group (Scheme42). On the basis of the strong affinity between phosphorus and oxygen and previouso bservations that Cs 2 CO 3 can attack at the positive phosphorus in tetra-arylphosphonium salts to produce nucleophilic aryl species, [106] it is suggested that direct attack of the carbonate anion at the positive phosphonium to give the five-coordinate phosphorus species D may be possible. [107] The The authors [108a] also applied the protocol to biologically active compounds, for instance, difluoromethylation of as tigmasterol acetate derivative,w hich affords product 266 in 53 % yield.…”
Section: Scheme40 Difluoromethylation Of Aliphatic Alcoholsmentioning
confidence: 99%
“…Various papers are published by discussing the role of individual salts, their selective way of transformation, role in asymmetric synthesis and many more. Some of the recent influencing research on application of salts in organic synthesis are use of diaryliodonium salts for novel arylation [20], applications of ferrocenium salts [21], salt as linker source [22], pyridinium salts as radical reservoir [23], use of vinyliodonium salts for alkenylation of nitriles [24], use of sulfonium salts for synthesis of spirocyclopropanyl paradienones [25], use of phosphonium salts for selective functionalization of pyridines [26], tropylium salts as lewis acid to catalyze acetalization and transacetalization [27], use of Phenyltrimethylammonium salts in nickel-catalyzed methylation of C− H bonds [28], aryldiazonium salts for carbohydroxylation of styrenes [29], synthesis of bicyclic aziridines from pyridinium salts [30], nucleophilic arylation with tetraarylphosphonium salts [31], application of trimethylsilanolate alkali salts in organic synthesis [32], use of α, β-unsaturated acylammonium salts for asymmetric organocatalysis [33], review on cesium salts use in organic synthesis [34], iodonium salts as benzyne precursors [35], use of bunte salts as a sulfur source for synthesis of 3-thioindoles [36], and C− H functionalization of arenes by diaryliodonium salts [37] etc.…”
Section: Diversified Use Of Salts In Organic Synthesismentioning
confidence: 99%